Solid Oxide Cell and Stack Testing, Safety and Quality Assurance (SOCTESQA). (2nd June 2015) - Auer, Corinna; Lang, Michael; Couturier, Karine; Nielsen, Eva Ravn; McPhail, Stephen J.; Tsotridis, Georgios; Fu, Qingxi; Chan, Siew Hwa
Abstract : In the EU-funded project "SOCTESQA" partners from Europe and Singapore are working together to develop uniform and industry wide test procedures and protocols for solid oxide cells and stacks SOC cell/stack assembly. New application fields which are based on the operation of the SOC cell/stack assembly in the fuel cell (SOFC), in the electrolysis (SOEC) and in the combined SOFC/SOEC mode are addressed. This covers the wide field of power generation systems, e.g. stationary SOFC µ-CHP, mobile SOFC APU and SOFC/SOEC power-to-gas systems. This paper presents the results which have been achieved so far. Besides a summary of existing test procedures a so called "test matrix" was created. This document includes generic test modules, e.g. current-voltage curves, electrochemical impedance spectroscopy, thermal cycling, electrical current cycling and long-term tests both under steady -state and dynamic operating conditions. The application specific test programs are created by combining several of these test modules.